Psychological Crisis of systematic Analysis and Management Strategy of University in Shandong of Chaina - Yao, Sun; Phromphithakkul , Wasin (Nimitmai Review Journal, 2024)
This Article aimed to study psychological crisis of systematic analysis and management strategy of university in Shandong of China. A target population of 134,580 college students studying in six universities in Yantai, Shandong Province was selected. A purposive sampling method was used to draw a sample of 439 according to the formula of Yamane equation, and the instrument used to collect data was a questionnaire. In this paper, a quantitative study was conducted using questionnaires. The tools used for the analysis were demographics, correlation analysis and AMOSS.26 analysis. Results: stressful life events (57.88 ± 20.58), psychological vulnerability (49.68 ± 13.87), psychological crisis ((10.2 ± 10.07), total score of stressful life events was positively correlated with psychological crisis performance score (r=0.605, p<0.05) and with total score of psychological vulnerability (r=0.0.735, p< 0.05); psychological The total psychological vulnerability score was positively correlated with the psychological crisis performance score (r = 0.716, P<0.05). Psychological vulnerability partially mediated the relationship between life events and psychological crisis, with a partial mediation effect of 0.301, accounting for 71.32% of the total effect. Conclusion Stressful life events can have both a direct effect on psychological crisis of college students and an indirect effect on psychological crisis through the level of psychological vulnerability. We should actively pay attention to the effects of stressful life experiences on college students' psychological well-being, reduce the sources of stressful crises, strengthen mental health education, and adopt suitable Strategy for psychological crisis management in colleges and universities. it can be concluded that the factors that cause the psychological crisis of Shandong college students in China mainly include four aspects. 1. Personal reasons 2. Family factors:3. School factors 4. Social factors.